Graphene based microstrip patch antenna on photonic crystal substrate for 5G application - Kumar, Chandan; Raghuwanshi, Sanjeev Kumar; Kumar, Vikram (Frontiers in Materials, 2022)
One of the strongest and thinnest substances known to exist is graphene. It can be efficiently used for antenna fabrication and significant benefits can be analyzed such as size miniaturization, gain and return loss enhancement, flexibility and increase in bandwidth, etc. In this paper, a graphene patch antenna has been designed and fabricated for 5G applications at 28.3 GHz. Different 5G frequency allocation throughout the world is shown in tabular form. Photonic crystal substrate is used to reduce surface wave loss which in turn, increases the radiation efficiency of the antenna. The ground plane is made up of copper, treated as a Perfect Electric Conductor (PEC). Several unique properties of graphene are analyzed and shown. Then, a thin graphene sheet is used as a patch and an antenna is designed and fabricated. The patch has dimensions of 3.4 mm by 2.38 mm. The simulated return loss is maximum at -33.69 dB at 28.3 GHz, whereas for the measured design it is -26.31 dB at 28.04 GHz. It is observed that graphene can be a good alternative to existing conductors, especially at higher frequencies. The proposed antenna is designed and simulated using HFSS software.